Can peer mentoring improve online teaching effectiveness? An RCT during the COVID-19 pandemic - Hardt, David; Nagler, Markus; Rincke, Johannes (Labour Economics, 2022)
Online delivery of higher education has taken center stage but is fraught with issues of student self-organization. We conducted an RCT to study the effects of remote peer mentoring at a German university that switched to online teaching due to the COVID-19 pandemic. Mentors and mentees met one-on-one online and discussed topics like self-organization and study techniques. We find positive impacts on motivation, studying behavior, and exam registrations. The intervention did not shift earned credits on average, but we demonstrate strong positive effects on the most able students. In contrast to prior research, effects were more pronounced for male students<br
CRIS-Team Scopus Importer:2022-07-22
Keywords: Chancengleichheit